The Financing and Redeployment of Specific Assets - Habib, Michel A.; Johnsen, D. Bruce (Journal of Finance, 1999)
We model the role various forms of nonrecourse secured debt play in efficiently redeploying assets whose value is state‐specific. Ex ante, an entrepreneur and an asset redeployer make noncontractible state‐specific investments in the primary and next‐best uses of an asset, respectively. The redeployer provides a secured nonrecourse loan equal to the value of the asset in the critical state that separates the good and bad states. In the event of a bad state, this contract averts ex post bargaining over the asset's quasi‐rents on redeployment and leaves the parties' ex ante investments undistorted.